Penjatuhan Pidana Tambahan Berupa Pembayaran Biaya Penanganan Perkara bagi Pelaku Tindak Pidana Korupsi - FIRA, FIRA MUBAYYINAH (At-Tuhfah : Jurnal Studi Keislaman, 2021)
This study focuses on additional criminal ideas in the form of payment of case handling fees for perpetrators of corruption. As normative legal research, this research uses a philosophical and legislative approach. This study reveals that payment of case handling fees is an important element in realizing the deterrent effect in sentencing. The more severe the punishment was given to the perpetrators of corruption is believed to reduce the desire and influence the decisions of potential perpetrators. The idea of ??prevention requires the existence of criminal penalties. The high rate of corruption is alleged as result the lightness of the punishment given to the perpetrators of corruption. ?